Back Cover: Graphene‐Driven Metadevice for Active Microwave Camouflage with High‐Efficiency Transmission Window (Small Methods 2/2021). Issue 2 (12th February 2021) - Huang, Cheng; Yang, Jianing; Ji, Chen; Yuan, Liming; Luo, Xiangang
Abstract : In article number 2000918 by Xiangang Luo and co‐workers, an electrically tunable metadevice driven by graphene is presented, which can achieve dynamical manipulation of the reflected wave magnitude and meanwhile generate an electromagnetic transparent window at two distinctive frequency bands. Using the above two functionalities, this metadevice can not only be developed for wideband adaptive camouflage, but also treated as an antenna radome for signal transmission.